Care seeking for childhood pneumonia by rural and poor urban communities in Lucknow: A community-based cross-sectional study - Anurag Minz; Monika Agarwal; J V Singh; V K Singh (Journal of Family Medicine and Primary Care, 2017)
Context: Globally, around 16% of under-five children die due to pneumonia. Childhood pneumonia, if identified early is a readily treatable through low-cost antibiotics. Access to timely and appropriate care is a key action to control pneumonia. Aims: The aim of the study was to understand the caregiver's care-seeking behavior for the management of childhood pneumonia among rural and urban poor communities in Lucknow. Settings and Design: Rural areas and urban slums of Lucknow district, from September 2014 to August 2015. Subjects and Methods: A community-based cross-sectional study. Total of 1065 under-five children were selected by multistage random sampling method. Caregivers of children (<5 years of age) were interviewed through pretested, semi-structured interview schedule. Information was gathered on episode of cough, difficult breathing, and or chest indrawing in child within 2 weeks preceding the survey, and caregiver's treatment seeking practices. Results: Out of total 1065 children, 52 (%) had pneumonia within 2 weeks preceding the survey. At the onset of illness, difficult/fast breathing was identified by 86.5% caregivers, but majority of them did not perceive it as a serious condition and resort to home remedies. Only 9.6% sought appropriate care at onset of illness. Appearance of chest indrawing in the child was identified by caregivers as a serious condition and sought treatment from outside. The mean time taken from onset of illness to the seeking care from health facility was around 2½ days (2.39 ± 0.75). Qualified private practitioners (70.5%) were the preferred choice and majority (87.0%) of the children received antibiotic for pneumonia. However, even after perception of seriousness of the illness, 26.8% and 11.1% caregivers in urban slums and rural areas, respectively sought inappropriate care at the first consultation. Conclusions: Caregivers were unable to perceive the severity of fast breathing leading to the delayed initiation of the appropriate treatment. There is a need of community mobilization through behavior change communication interventions to promote early symptom recognition and appropriate care seeking for pneumonia.